2008
DOI: 10.1007/s12088-008-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas sp. to Sphingobium indicum: a journey of microbial degradation and bioremediation of Hexachlorocyclohexane

Abstract: The unusual process of production of hexachlorocyclohexane (HCH) and extensive use of technical HCH and lindane has created a very serious problem of HCH contamination. While the use of technical HCH and lindane has been banned all over the world, India still continues producing lindane. Bacteria, especially Sphingomonads have been isolated that can degrade HCH isomers. Among all the bacterial strains isolated so far, Sphingobium indicum B90A that was isolated form HCH treated rhizosphere soil appears to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…74,2010 MICROBIAL DEGRADATION OF HCH 59 the environment with lower HCH concentrations due either to dispersal from stockpiles or to the use of the insecticide. The majority of HCH waste has been discarded in the open or stored at various levels of containment near the production sites, although in some cases, the top layer of soil at such sites has been removed for use in filling material for the construction of roads and buildings (97,145,181).…”
Section: Fig 2 Known Locations Of Hch Dumps In Excess Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…74,2010 MICROBIAL DEGRADATION OF HCH 59 the environment with lower HCH concentrations due either to dispersal from stockpiles or to the use of the insecticide. The majority of HCH waste has been discarded in the open or stored at various levels of containment near the production sites, although in some cases, the top layer of soil at such sites has been removed for use in filling material for the construction of roads and buildings (97,145,181).…”
Section: Fig 2 Known Locations Of Hch Dumps In Excess Ofmentioning
confidence: 99%
“…As with anaerobic degradation, essentially no work has yet been done on the biodegradation of the relatively unstable ε-HCH. Most of the HCH-degrading aerobes known to date are members of the family Sphingomonadaceae (74,75); so far, 30 HCHdegrading sphingomonads from different parts of the globe have been reported (Table 1). It is not clear how soon after the first use of HCH these strains emerged; the first strain was reported in the late 1980s from Japan (155), but reports from other countries quickly followed.…”
Section: Aerobic Degradationmentioning
confidence: 99%
“…There are also some microbial species (e.g. Sphingobium indicum, Lal et al 2008) reported for the bioremediation of HCH isomers. However, many onsite studies reveal that the survival and performance of the isolated microorganisms in real contaminated sites was not promising.…”
Section: Recommendations and Perspectivesmentioning
confidence: 99%
“…The severity of the problem is reflected from the fact that HCH residues continuously are detected in air, soil, vegetation and water samples and even in some pristine ecosystems like Arctic region, Antarctica, Pacific Ocean, etc. (USEPA 1980;Iwata et al 1994;Willet et al 1998;Walker et al 1999;Lal et al 2008). The chemical properties of HCH isomers such as low water and high fat solubility, stability to photooxidation and low vapour pressure are the main factors attributing their persistence in the environment (Willet et al 1998;Walker et al 1999).…”
mentioning
confidence: 99%
“…Many Gram-negative bacteria have been reported to have metabolic abilities to attack lindane. Sphingobium japanicum UT26, Sphingobium francense SpC, Sphingobium indicum B90A, and Sphingobium ummariense among other strains belonging to the Sphingomonadaceae family (Dogra et al 2004;Boltner et al 2005;Lal et al 2006;Mohn et al 2006;Nagata et al 2007;Lal et al 2008;Singh & Lal 2009) and fungi such as Pleurotus eryngii, Trametes hirsutus, Cyathus bulleri, and Phanerochaete sordida (Singh & Kuhad 2000;Quintero et al 2008) have been reported to degrade the pesticide.…”
Section: Introductionmentioning
confidence: 99%